The molecular structures of chlorpromazine and thiethylperazine and a discussion of the action mechanism of the phenothiazine derivatives - McDowell, Jocelyne Jessica Helen (Department of Physics, 2016)
A very important group of the derivatives of phenothiazine are termed the major tranquillizers. The introduction into clinical psychiatry by Delay and Deniker in 1952 of chlorpromazine and its analogues has revolutionized the treatment of psychotic conditions and of mental diseases in general. Although the phenothiazines have been subjected to extensive clinical tests, their chemical structural features have not so far been found to have a sufficiently constant association with pharmacological, psychological and clinical effects to develop a theory of their mode of action. The phenothiazines are divided into three groups according to the chemical nature of the side chain attached to the nitrogen atom:- (1), dimethylamino-propyl, (2), piperidine, and (3), piperazine radical. Chlorpromazine, pyscho-tropically potent, belonging to the first group, and thiethylperazine, with relatively little tranquillizing or sedative action, belonging to the third, were chosen for complete structural analyses and are reported in Sections B and C respectively. The original intention was to determine the structure of phenothiazine for comparative purposes, but information was received during the course of the present study that its structure had been solved. Crystal data on phenothiazine and on another derivative, chlorpromazine hydrochloride, form the subject of Section A. Chlorpromazine, one of the best known of the series, is 3-chloro-10 (3' dimethyl-amino-n-propyl) phenothiazine. It is the valuable drug Largactil used in general medicine (for relief of nausea and vomiting, and radiation sickness), psychiatry (to control schizophrenic or manic states), surgery and anaesthesia (to modify or prevent traumatic and haemorrhagic shock). The drug has a depressant action on the brain stem, with little or no action on the cerebral cortex or the spinal cord. (Colloquium, Paris, 1955; Buxton Hopkin, 1955; Courvoisier, Fournel, Ducrot, Kolsky & Koetschet, 1953; Takayanagi, 1964). Thiethylperazine (trade name Torecan) is 2-ethylthio- 10-[3-(4-methylpiperazine-1-yl) propyl] phenothiazine. It is valued mainly for its antiemetic properties and is used for the control of postoperative vomiting, vomiting associated with malignant disease, radiation therapy, etc. (Progress in Drug Research, 1963; Extra Pharmacopoeia, 1967). The study of the series has been undertaken with the eventual hope of correlating molecular structure with psycho-pharmacological properties. It seems likely that in seeking the precise mechanism of action of the drugs, the problems must be "viewed through the glasses of the submolecular". (Szent-Gyorgyi, 1960). Section D gives a brief description of the properties of the drugs and outlines a possible relation between the molecular structure and the action mechanism. Section A in abridged form has been published (Feil, Linck & McDowell, 1965, Nature) and condensed versions of Sections B and C have been submitted for publication to Acta Crystallographica (McDowell, Chlorpromazine, accepted Dec. 1968; McDowell, Thiethylperazine, accepted Sept. 1969). The structure of chlorpromazine is the first of the phenothiazines to have been solved.